Cultural identity and new communication technologies political, ethnic and ideological implications - Wachanga, D. Ndirangu (Gale Virtual Reference Library, 2011)
Presents a blend of conceptual, theoretical and applied research in NCTs (New Communication Technologies). Examines content that places new communication technologies in a context that recognizes their seamless co-option into the designs of politics and culture.